(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Growing number of Dengue patients posed a threat to the community. It also stood with a great deal of challenge to the physicians working in the hospitals and treating the pediatric patients yet looking for a straightforward approach to deal with severe cases of Dengue. Observing the low albumin status in every single Dengue Shock Syndrome (DSS) the concept of arresting the progression of DF (Dengue Fever) to DSS (Dengue Shock Syndrome) came in our mind. Therefore, the study topic was selected as “Role of albumin infusion in treatment outcome and preventing DSS in children with DF: A quasi purposive study.” Objective: The objectives of the study were to observe the status of albumin of DF, the relationship of Albumin with Platelets, the effect of albumin infusion on the progress of DF to DSS. Patients and Methods: This is a prospective quasi purposive study conducted in the department of Pediatrics at Bangladesh Specialized Hospital (BSH) from June 2022 to December 2022 in the age group of Pediatric patients (from more than 1 month eighteen years). All the patients admitted with DF or DSS during that period were included in the study. National Guideline of DF and DSS was followed to Diagnose and to hydrate the Dengue affected children. Albumin was administered to manage not only DSS but also DF children to prevent them from progressing to DSS. Journal of Bangladesh College of Physicians and Surgeons Vol. 41, Dengue Fever Supplement Issue, October 2023 They were managed following the national guideline. Additionally, Hct and Albumin status were closely monitored particularly on day five, six and seven of the disease. Albumin was administered according to the set protocol for this study. Results: A total of 44 cases were included in the study. Among them 28 DF and 16 DSS were diagnosed and documented in this study. Twenty-seven male and seventeen female children were admitted with common symptoms like Fever, bodyache, headache, abdominal pain, vomiting and loose motion. A total of thirty-six children were administered Albumin. Among them 21 were DF and 15 were DSS. In statistical analysis no significant difference was found in Age, Weight, Hematocrit (Hct), Ferritin on admission when compared between DF and DSS. No significant difference could be observed also in Hospital Stay as compared between the two groups. However, significant statistical differences were detected in Day 1, 2, 3 platelet levels and Day 1 and 2 Albumin levels. Neither any DIC nor any MISC, nor any death was recorded. No antibiotic was required. No Platelet transfusion, no IVIG, no Methylprednisolone, nor any other steroid was needed. No significant adverse effect was documented in administering Albumin. Conclusion: In this study it has been found that albumin is safe to use in children with DF to prevent DSS. It also is effective in reducing morbidity in Dengue affected children. J Bangladesh Coll Phys Surg 2023; 41: 51-62